2021
DOI: 10.1108/fs-12-2020-0133
|View full text |Cite
|
Sign up to set email alerts
|

University-industry collaborations in Pakistan: current challenges and future opportunities

Abstract: Purpose This paper aims to identify current challenges that hinder university–industry (U-I) collaboration in Pakistan and presents future opportunities for promoting such collaborations in developing countries. Design/methodology/approach This exploratory study presents new empirical evidence obtained from Pakistan via a questionnaire survey of 24 universities, 25 interviews with key stakeholders including industry managers and outputs from a high level workshop event. Findings Although there is limited e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Policy/legal framework: A policy or legal framework is required for successful HEI–industry collaboration (Awasthy et al, 2020; Malik et al, 2021; Sjoo and Hellstrom, 2019). In this regard, all focus groups observed the absence of a clearly stated policy and legal framework detailing how polytechnics should collaborate with industry and then suggested that the government should formulate policies and laws that would stimulate, facilitate and regulate collaborative activities between polytechnics and industry:‘[…] to promote polytechnic–industry collaboration in the country, the government has a major role to play.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Policy/legal framework: A policy or legal framework is required for successful HEI–industry collaboration (Awasthy et al, 2020; Malik et al, 2021; Sjoo and Hellstrom, 2019). In this regard, all focus groups observed the absence of a clearly stated policy and legal framework detailing how polytechnics should collaborate with industry and then suggested that the government should formulate policies and laws that would stimulate, facilitate and regulate collaborative activities between polytechnics and industry:‘[…] to promote polytechnic–industry collaboration in the country, the government has a major role to play.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, industry benefits by gaining access to technological knowledge, world-class academics, obtaining answers to specific problems, enhanced R&D productivity, enhancement of reputation, financial support for expensive projects and the acquisition of competitive advantage (Gattringer et al, 2014). HEI–industry collaboration takes different forms, including joint research projects or conferences, student placements, consultancy by lecturers, research contracted to lecturers by industry, industry input into curriculum development and the training of employees in industry (Ishengoma and Vaaland, 2016; Malik et al, 2021). It has been argued that effective HEI–industry collaboration is necessary to deliver high-quality educational outcomes.…”
Section: Hei–industry Collaborationmentioning
confidence: 99%
“…While Chan et al (2002) alluded to increase in revenues, higher research productivity and easy of patenting as motivation for UIC, Awasthy et al (2020) hinged on organizational commitment and availability of resources through networks as a precursor for UIC. Another area that deepens UIC is the area of staffing/academic mobility (staff exchange) (Malik et al, 2021). This relates to the movement of academic staff and researchers to the FEBE industry for a scheduled period of time to understudy the practices with a view to discovering the industry problems and be able to formulate research direction and agenda.…”
Section: Areas Of Collaboration Between University and Industrymentioning
confidence: 99%
“…While UIC has gained ground, considerably, in developed economies; it has progressed slowly in developing economies (Malik et al, 2021). In this regard, there is a great concern about the collaboration between university and industry.…”
Section: Introductionmentioning
confidence: 99%
“…therefore an academic level, there must be a proper balance between research and teaching, as research is critical for faculty development and academic effectiveness (Salman et al, 2018). In Pakistan, and in most of underdeveloped countries, university-industry collaboration has grown slowly, many industrialised economies have previously encountered a situation where it took a long time for companies to recognise that collaborating with universities as a means of acquiring new scientific competencies and fresh ideas might be extremely beneficial to industrial research and development (Malik et al, 2021). The collaboration of universities and industries in Pakistan has not been adequately recognized particularly by the private sector, as a result the concept of university-industry linkage is rarely used in context of Pakistan (Bashir et al, 2010).…”
Section: Literature Review University Performancementioning
confidence: 99%